The use of sunscreen products among final year medicine and pharmacy students: a cross‑sectional study of knowledge, attitude, practice, and perception - Awadh, Ammar Ihsan JawaD; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod; Ab. Hadi, Hazrina (Wolters Kluwer - Medknow, 2016)
Objective: To evaluate the knowledge, attitude, perception, and practice of medical and pharmacy students toward the usage of sunscreen as protection for the skin against ultraviolet (UV) radiation. Methods: This cross-sectional study was conducted among final year medical and pharmacy undergraduates at the International Islamic University Malaysia (IIUM). Validated questionnaires were distributed to 134 medical students and 100 pharmacy students. Descriptive and inferential statistics were used where appropriate. Findings: 161 out of 234 participants completed the questionnaires. The participants comprised 101 medical students (75.4%) and 60 pharmacy students (60.0%). The majority of the respondents were females (102; 63.4%) and 59 (36.6%) were males. The median of the knowledge scores of the final year medical students was significantly lower than that of the final year pharmacy students (p < 0.001). The female students showed significantly higher knowledge scores than the male students (p = 0.027). This study reported that 24 (39.3%) pharmacy students were influenced by the media to use sunscreen, whereas 35 (34.7%) medical students were influenced the most by friends to use sunscreen. The final year pharmacy students had a better perception compared to the medical students, with the total perception score of the final year pharmacy students being significantly higher than that of the final year medical students (p = 0.020). Most of the participants were also aware of the harmful effects of UV radiation and had a positive reaction towards the usage of sunscreen to prevent those harmful effects. Conclusion: In conclusion, the knowledge and perception of final year pharmacy students was significantly higher than the knowledge and perception of final year medical students with regard to the usage of sunscreen.